2011
DOI: 10.1177/1078155211402104
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing pain relief in a specialized outpatient palliative radiotherapy clinic: Contributions of a clinical pharmacist

Abstract: The CP plays a key role in holistic patient assessment and optimization of pharmacologic therapy, contributing to improved symptom control of patients receiving palliative RT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 26 publications
1
50
0
Order By: Relevance
“…Similarly the RAPRP brain metastases clinic is staffed by a radiation oncologist, a nurse practitioner, a radiation therapist, a social worker, an occupational therapist and a dietician [22]. Medication counseling took place in 84% of all visits: 88% of the time opioid toxicity screening was needed, 86% of the time bowel routines were addressed, 29% of the time a change in analgesics was recommended and 17% of the time communication with a c ommunity pharmacy was required [31]. This program has published a follow-up report as well, which further demonstrates how multidisciplinary assessments contributed to improvements in patient reported pain relief, tiredness, depression, anxiety, drowsiness and overall well being 4 weeks after the day of initial assessment [30].…”
Section: Collaboration With Allied Oncology Professionalsmentioning
confidence: 99%
“…Similarly the RAPRP brain metastases clinic is staffed by a radiation oncologist, a nurse practitioner, a radiation therapist, a social worker, an occupational therapist and a dietician [22]. Medication counseling took place in 84% of all visits: 88% of the time opioid toxicity screening was needed, 86% of the time bowel routines were addressed, 29% of the time a change in analgesics was recommended and 17% of the time communication with a c ommunity pharmacy was required [31]. This program has published a follow-up report as well, which further demonstrates how multidisciplinary assessments contributed to improvements in patient reported pain relief, tiredness, depression, anxiety, drowsiness and overall well being 4 weeks after the day of initial assessment [30].…”
Section: Collaboration With Allied Oncology Professionalsmentioning
confidence: 99%
“…14 Several publications indicated that the inclusion of pharmacists in interdisciplinary pain teams successfully decreased drug-related problems and demonstrated initial and prolonged pain relief. [14][15][16][17] A meta-analysis of 4 studies by Edwards et al in February 2019 confirmed that pharmacist educational interventions for patients with cancer pain showed promise in reducing pain intensity. 18 In view of this fact, Chinese clinical pharmacists are trying to participate in the multidisciplinary management of cancer pain by providing a professional pain medication guide and helping patients effectively control pain.…”
Section: Introductionmentioning
confidence: 99%
“…Positive effects of educational interventions that pharmacists delivered to patients with chronic pain have been reported 11. Moreover, in outpatients receiving palliative care, pharmacists have been shown to contribute to optimised pain therapy and symptom control 12. As previously reported,13 multidisciplinary pain management including interventions by pharmacists increases guideline adherence and even improves the patients’ individual pain situation.…”
Section: Introductionmentioning
confidence: 87%